Manufacturing Different Types of Solid Dispersions of BCS Class IV Polyphenol (Daidzein) by Spray Drying: Formulation and Bioavailability - Gean Pier Panizzon; Fernanda Giacomini Bueno; Tânia Ueda-Nakamura; Celso Vataru Nakamura; Benedito Prado Dias Filho (MDPI AG, 2019)
Daidzein (DZ) is a polyphenolic compound belonging to Biopharmaceutical Classification System class IV, which shows that it may have limited therapeutic effects due to its low solubility and poor bioavailability. This study aimed to obtain high-purity DZ and prepare and characterize different types of solid dispersions (SDs) in order to enhance aqueous solubility and bioavailability. Excipients were investigated in order to manufacture different types of solid dispersions (SDs). Second-generation solid dispersions (SG), third-generation solid dispersions (TG), and second- and third-generation pH-modulated solid dispersions (SD and TG pHM-SD) were produced via spray drying. The SDs were characterized and tested for in vitro DZ release and oral bioavailability. SDs have shown increased aqueous solubility and in vitro release rate. Solid-state characterization showed that DZ was in an amorphous state in most of the formulations. The enhanced aqueous solubility of TG-pHM SD was reflected by an increase in oral bioavailability, which significantly increased the maximum plasma concentration approximately 20-fold and decreased the time to reach the maximum plasma concentration. The production of pHM SDs that contain DZ via spray drying is a simple and effective approach for oral drug delivery, which has the potential to greatly reduce the dose and enhance therapeutics effects.